Cuts or carcasses? Diet form affects fecal microbial and animal fiber fractions in a large carnivore, the Asiatic lion - Mengmeng Sun; Annelies De Cuyper; Yunhan Zhang; Marcus Clauss; Anouk Fens; Linda G. R. Bruins-van Sonsbeek; Geert P. J. Janssens (PLoS ONE, 2025)
The care of exotic felids in zoos involves numerous factors, and the dietary management is currently considered particularly critical. This study investigated the effects of four different dietary regimens on the fecal microbiota and fecal characteristics of four female Asiatic lions ( Panthera leo persica ) at the Rotterdam Zoo, the Netherlands. The lions were sequentially fed beef meat on bone (BM01, 4 weeks), degutted and skinned cattle carcasses (CC, 4 weeks), degutted but unskinned banteng carcasses (BC, 2 weeks), and then returned to beef meat on bone (BM02, 4 weeks). Feces were collected at day 28, 56, 70 and 98, and represented the total feces of the group between the last feeding and the next feeding. 16S rRNA gene sequencing showed significant microbial shifts at phylum level, including, between CC and the subsequent diets, a decrease in Proteobacteria abundance and increases in Actinobacteria and Fusobacteria (p < 0.05). Fecal characteristics varied by diet. CC resulted in the highest proportion of visible bone, and BC in the lowest. Fecal particle size was highest on BC, and fecal volume on BC was about twice that of other feeding regimes, suggesting a dilution by indigestible skin and fur components. Significantly lower levels of fecal ash, calcium and phosphorus on BC (p < 0.001) supported the dilution hypothesis. On all diets, ash was shown to be a significant part of the animal fiber in the feces (p < 0.001). Although unskinned carcass may have required greater chewing effort, potentially increasing bone fragmentation, the reason for the reduced bone intake remains unclear. While the exact intake of animal fiber could not be quantified, differences in microbial composition and fecal characteristics were associated with variations in the type of animal fiber, such as bone versus skin.